دراسة تحليلية في علم مصطلح الحديث: المعنعن والمؤنأن أنموذجاً = An anlaytical study in the science of Hadith terminology: 'An'anah and An'anah as examples - Mohammed Zayd, Alsanousi Amhimmid; Mohammed Yaqub, Mohammed Abullais Shamsuddin; Ibrahim, Hassan Ahmed (Kulliyyah of Revealed Knowledge And Human Sciences, International Islamic University Malaysia, 2019)
تناول هذا البحث بالدراسة والتحليل لمصطلح حديثي من أهم مصطلحات علوم الحديث، ألا وهو الحديث المعنعن والمؤنأن، وعمل البحث على تجلية وبيان مفهوم الحديث المعنعن والمؤنأن والذي يعتريه بعض الغموض من حيث اتصاله وانقطاعه، مما أدى ذلك لتصحيح بعض الأحاديث والعكس من غير تحري الدقة في شروطه وما قرره علماء هذا الشأن، ويعمل هذا البحث على تحليل وبيان مراد معنى هذا المصطلح، مع ذكر شروطه المضبوطة التي قررها علماء الحديث حتى يستطيع المشتغل بالحديث أن يحكم عن الحديث بما هو صواب، وتبرز أهمية هذا البحث في ضمان الحفاظ على السنة النبوية والتي تعتبر المصدر الثاني لديننا الحنيف، وسار الباحث على منهجين المنهج الاستقرائي والذي يعنى باستقراء كتب علوم الحديث وأقوال العلماء الأثبات في ذلك حتى تكمن لنا مادة علمية جامعة وبدورها يقوم منهج النقد ويتمثل في النظر لأقوال العلماء وبيان الراجح من أقوالهم وتوجيهها توجيها سليما، وأثبتت الدراسة أن الحديث المعنعن والمؤنأن من الأحاديث المقبولة بشروط ومن أهمها وأعظمها أن يتحقق فيه المعاصرة وهذا القول الذي رجحناه مع ذكر الأدلة على ذلك. *********************************************************** This study analyses one of the most important terms of Hadith Terminology, which is the hadiths narrated in the form of 'from' (ʿanʿanah) and 'that' (ʾanʾanah). The study attempts to clarify the definition of hadiths narrated in the form of 'from' and 'that' which are vague in terms of the cohesiveness or interruption of the chain of narrators. This uncertainty incorrectly led to labeling some hadiths as sound and others as weak without a close inspection of the conditions of hadith grading and the scholarly rules that were set for this field. The study aims to analyze and clarify the meaning of this term and mention the precise conditions that were set by scholars of hadith in order for the practitioner in the field of hadith to correctly judge a hadith. The importance of this study is underlined by the guarantee of the preservation of the Prophetic Sunnah, which is the second legislative source of our perfect religion. Throughout this study, the author followed two approaches: 1) the inductive approach, which aims to extrapolate a comprehensive scholarly content through the thorough investigation of the books of hadith sciences and the statements of the great scholars; 2) the critical approach, which explores the statements of scholars and demonstrates the most correct ones, in order to understand them in an accurate manner. The study demonstrates that hadiths narrated in the form of 'from' and 'that' are among the conditionally-accepted hadiths; the most important of those conditions is the contemporariness. This is the opinion we have deemed to be most correct, and supported this view with evidence.